Role of P27kip1 Protein, P45skp2 Coactivator, and P38jab1 Coactivator in Preventing Rhabdomyosarcoma (RMS) in Oral Cavity of Children - Inne Suherna Sasmita; Ratna Indriyanti; Willyanti Soewondo (Majalah Kedokteran Bandung, 2022)
Rhabdomyosarcoma is a rare malignant tumor that attacks the differentiation of skeletal muscle and usually affects children, contributing to about 60% of all soft tissue sarcomas. The purpose of this study was to examine the relationship between p27Kip1 immunoexpression and p45Skp2 and p38Jab1 coactivators, as well as the relationship between p27Kip1 immunoexpression and p45Skp2 and p38Jab1 coactivators on stages and prognosis of oral RMS in children. This was a restrospective study on the immunoexpression of p27Kip1 and p45Skp2 and p38Jab1 coactivators on RMS cells. The RMS stage was determined according to the American Joint Committee of Cancer/AJCC of stages 1–4, and were divided into group I (stages 1 and 2) and group II (3 and 4). Samples were retrieved fromt he paraffin blocks of patients with embryonal RMS. Each paraffin block was cut, and 6 samples with 5 µm thickness from each block were examined using p27Kip1, p45Skp2, and p38Jab1 proteins. The analysis was performed using a linear regression test on the relationship between p27Kip1 and p45Skp2 and p38Jab1, resulting in a p-value of 0.000 (<0.05) and a coefficient value of b -1.36. Meanwhile, the stage was analyzed  using the Wald test of 8.0688, resulting in a p-value   of 0.0045 with a significant negative correlation. Analysis on the relationship between p45Skp2 and p38Jab1 and the RMS stage was performed using the Gamma test, resulting in a significant positive correlation (p<0.05).